The Effect of Work Ethics on the Teacher's Performance of State Madrasah Ibtidaiyah in Medan City - Rizki Utami Batubara; Darwin Darwin; Yuniarto Mudjisusatyo (RIRAI Publisher, 2023)
This study aims to determine the effect of work ethic on teacher performance. This type of research uses quantitative research with a path analysis approach with a population of 281 State MI teachers in Medan City. Sampling was carried out by Proportional Random Sampling with a total sample of 164 and data collection was carried out using a questionnaire. The questionnaire used was first tested to obtain a valid and reliable instrument. Prior to testing the instrument, a requirements analysis test was carried out as a path analysis requirement, namely the normality test and linearity test. The results of the research findings are that there is a positive direct effect between work ethic on teacher performance.